Relationship Between Reliability and Cost of Performance Assessment - Parkes, Jay (Education Policy Analysis Archives, 2000)
Performance assessments have come upon two major roadblocks: low reliability coefficients and high cost. Recent speculation has posited that the two are directly related such that cost must rise in order to increase reliability. This understanding may be an oversimplification of the relationship. Two empirical demonstrations are offered to show that more than one combination of sources of error may result in a desired generalizability coefficient and that it is possible to increase the number of observations while also decreasing cost.